Generating technology development paths to the desired future through system dynamics modeling and simulation - Chen, Hongyi; Yu, Jiang; Wakeland, Wayne (Futures : the journal of policy, planning and futures studies, 2016)
•Technology foresight provides valuable information to individual companies.•System dynamics modeling is very useful in linking technology foresight to planning.•We develop an innovation diffusion model via system dynamics simulation.•Individual companies can use the model to visualize technology development paths.•Critical technology development factors can be identified and tested using the model Technology foresight is usually conducted by government or industry associations and can serve to provide companies with information on critical technologies that a country or industry intends to develop in the next ten to twenty years. For individual companies to benefit from foresight results and transform them into specific technology development plans, the relationships between the desired technologies and the dynamic business environment need to be understood. In this article, an innovation diffusion model implemented via system dynamics simulation is used to operationalize the link between foresight and planning. It helps company decision makers visualize the diffusion process of the innovation inhabiting the chosen technology and determine the critical parameters quantitatively through experiments and analysis. Using these results, possible paths leading to the desired future of the chosen technology can be generated and plans be prepared to guide the effective development of the technology, essential infrastructure, and key applications. An example is presented at the end to illustrate the application of the proposed method that helps a Chinese service carrier to plan for its 4G wireless communication network expansion.